Instruments for assessing organisational food environments of workplaces: a scoping review - Ana Beatriz Coelho de Azevedo; Patricia Gálvez Espinoza; Fernanda Martins de Albuquerque; Cintia Chaves Curioni; Daniel Henrique Bandoni; Daniela Silva Canella (Public Health Nutrition)
Abstract